Exosomal LINC01213 Plays a Role in the Transition of Androgen-Dependent Prostate Cancer Cells into Androgen-Independent Manners. (10th March 2022) - Guo, Zhuifeng; Lu, Xuwei; Yang, Fan; He, Chang; Qin, Liang; Yang, Ning; Han, Conghui; Wu, Jiawen
Abstract : Background . Castration-resistant prostate cancer (CRPC), one of the prostate cancers, is a medical conundrum around the world. Some studies have demonstrated that many long noncoding RNAs in exosomes are very important in many types of cancer, including prostate cancer. However, until now, the function of exosomes in the occurrence and development of CRPC has not been reported. Methods . In vitro, cell coculture was used in LNCap cells and PC-3 cells, while the isolation and purification of exosomes and the subsequent treatment assays were used in functional studies. In vitro assays were performed to detect the transformation of ADPC cells (androgen-dependent prostate cancer) into AIPC cells (androgen-independent prostate cancer). Subsequently, a lncRNA-sequencing assay was performed to detect different lncRNA expression profiles in ADPC cells cocultured with or without AIPC exosomes. The role of LINC01213 was analysed by a TCGA database after silencing the expression of LINC01213. CCK-8, qRT-PCR, and Western blotting studies were performed to analyse the possible mechanism by which exosomes participate in prostate cancer progression. Results . In the coculture system, ADPC cells acquired androgen deprivation tolerance through exosome-mediated intercellular communication. Exosomes secreted by AIPC cells can promote the transformation of ADPC cells into androgen-independent cells in vitro and in vivo. lncRNA sequencing showed that LINC01213 was upregulated in exosomes derived from AIPC cell lines. The rescue experiments were preformed, and the results revealed that most of the functions of LINC01213 were performed by Wnt/ β -catenin. Conclusions . All the findings showed that exosomes play a key role in CRPC progression by upregulating LINC01213 and activating Wnt/ β -catenin signalling.